Investigating the roles of zinc finger homeobox 3 in circadian rhythms - Edwards, JK (2013)
This thesis describes a program of investigation carried out by the author at MRC Harwell that shows, for the first time, that the gene Zfhx3 plays a role in modulating the circadian clock. The work has used the short circuit (Sci) mouse model to assess the molecular and genetic role of Zfhx3 in circadian behaviour and visual processing.